2005
DOI: 10.1002/mus.20463
|View full text |Cite
|
Sign up to set email alerts
|

Motor evoked potentials in a mouse model of chronic multiple sclerosis

Abstract: We tested cortical motor evoked potentials (cMEPs) as a quantitative marker for in vivo monitoring of corticospinal tract damage in a murine multiple sclerosis model (experimental autoimmune encephalomyelitis, EAE). The cMEPs, previously standardized in naive C57BL/6 developing and adult mice, were studied longitudinally in adult EAE mice. Central conduction times (CCTs) increased significantly shortly before the earliest clinical signs developed (10 days postimmunization, dpi), with peak delay in acute EAE (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…Both immunohistological and cortical motor evoked potential studies have suggested there is a substantial diminution in corticospinal axon numbers in mice with long-standing MOG peptide EAE (Black et al, 2006; Amadio et al, 2006). Enumeration of specifically labeled corticospinal axons would be desirable to strengthen this conclusion.…”
Section: Resultsmentioning
confidence: 99%
“…Both immunohistological and cortical motor evoked potential studies have suggested there is a substantial diminution in corticospinal axon numbers in mice with long-standing MOG peptide EAE (Black et al, 2006; Amadio et al, 2006). Enumeration of specifically labeled corticospinal axons would be desirable to strengthen this conclusion.…”
Section: Resultsmentioning
confidence: 99%
“…Mice were anesthetized with trichloroethanol, 0.02 ml/g of body weight, and placed under a heating lamp to avoid hypothermia. Neurophysiological studies were performed as described (14,32). An unpaired Student's t test (2-tailed distribution, 2 samples with equal variance, α = 0.05) was performed for statistical evaluation of the data.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment with Ad-G/IL4 significantly improved also the neurophysiological parameters. Motor-evoked potentials (MEP)-used as a functional measure of corticospinal tract integrity 14 -were measured in C-EAE mice at 75 days post-immunization. MEP was recordable in 10/11 (91%) of the Ad-G/IL4-treated mice but in only 5/10 (50%) of the control, Ad-Gtreated mice (Po0.05, w 2 ).…”
Section: Intracisternal Delivery Of Ad-g/il4 Induces Clinical and Funmentioning
confidence: 99%